PIK3CA mutation in Chinese patients with lung squamous cell carcinoma - Yu, Jinglin (AME Publishing Company, 2013)
OBJECTIVE: To investigate PIK3CA mutation in Chinese patients with lung squamous cell carcinoma (LSCC) and explore their relationship with clinicopathological profiles. METHODS: Tumor samples from 123 cases of LSCC were included in this study. PIK3CA mutations in exon 9 and 20 were screened by pyrosequencing and confirmed by clone sequencing or amplification refractory mutation system (ARMS). Denaturing performance liquid chromatography (DHPLC) was employed for evaluation of EGFR mutation in exon 19, 21 and KRAS mutation. RESULTS: PIK3CA mutations were found in 3 (2.4%) patients. The mutation type included E545K, E452Q and H1047R. Of these three patients, one coupled with EGFR mutation, and the other two coupled with PIK3CA amplification. All the three patients shared the same clinicopathologic characteristics: male, less than 60 years old, had smoke history, stage III and carried wild-type KRAS. CONCLUSIONS: The frequency of PIK3CA mutation is low in Chinese patients with LSCC. The mutational status of PIK3CA is not mutually exclusive to EGFR mutation.